2005
DOI: 10.1111/j.1469-7610.2005.01426.x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal improvements in communication and socialization of deaf children with cochlear implants and hearing aids: evidence from parental reports

Abstract: The pattern of results suggests that cochlear implants may be effective in improving deaf children's communication and social skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
81
0
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 29 publications
12
81
0
7
Order By: Relevance
“…At the same time, it should be emphasized that after CI children may continue to demonstrate communication difficulties and variability in their development of spoken language (Purdy et al, 1995;Sach & Whynes, 2005;Spencer, 2004;Spencer & Marschak, 2003;Svirsky et al, 2000). Bat-Chava et al (2005) suggested that this variability might be evident in two situations: first, in the poor acoustics of listening conditions in which children find themselves (e.g., with background noise), and second, in differences in individual functioning among implanted children. In addition, children's progress is a long-term process; for example, speech intelligibility continues to significantly improve over an extended period (Chin, Tsai, & Gao, 2003;Tobey, Geers, Brenner, Altuna, & Gabbert, 2003;Peng, Spencer, & Tomblin, 2004).…”
Section: Problem Domainsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, it should be emphasized that after CI children may continue to demonstrate communication difficulties and variability in their development of spoken language (Purdy et al, 1995;Sach & Whynes, 2005;Spencer, 2004;Spencer & Marschak, 2003;Svirsky et al, 2000). Bat-Chava et al (2005) suggested that this variability might be evident in two situations: first, in the poor acoustics of listening conditions in which children find themselves (e.g., with background noise), and second, in differences in individual functioning among implanted children. In addition, children's progress is a long-term process; for example, speech intelligibility continues to significantly improve over an extended period (Chin, Tsai, & Gao, 2003;Tobey, Geers, Brenner, Altuna, & Gabbert, 2003;Peng, Spencer, & Tomblin, 2004).…”
Section: Problem Domainsmentioning
confidence: 99%
“…Moreover, great variability is often reported in children's outcomes following CI (Bat-Chava et al, 2005;Purdy, Chard, Moran, & Hodgson, 1995;Sach & Whynes, 2005;Spencer, 2004;Spencer & Marschak, 2003;Svirsky et al, 2000). This variability indicates that children may continue to demonstrate hearing and communication difficulties after CI.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These items were selected as they reflected areas reported by parents and children, clinically and in research studies, as being important in deaf children and/or improving after cochlear implantation (e.g. Edwards, Khan, Broxholme and Langdon, 2006;Huttunen & Välimaa, 2010;Anmyr, Larsson, Olsson and Freijd, 2012;Van-Gent, Goedhart & Treffers, 2012;Shin, Kim, Kim et al, 2007;Bat-Chava, Martin & Kosciw, 2005). Each of these factors was presented within a table and respondents were asked to tick the box to show how things have changed, indicating degree of change using the following scale: much worse; slightly worse; no change; slightly better; much better.…”
Section: Quality Of Life Itemsmentioning
confidence: 99%
“…(1997), as relações nterpessoa s que a cr ança estabelece é que serv rão de contexto para sua soc al zação, para a emergênc a de competênc as bás cas e para a aqu s ção de hab l dades de comun cação. Pesqu sadores têm ressaltado que é a mot vação para comun car-se verbalmente que apo a o desenvolv mento da l nguagem que, como as hab l dades comun cat vas, está fortemente relac onada às exper ênc as soc a s da cr ança (Ol ve ra, 2002;Bat-Chava, Mart n & Kosc w, 2005).…”
Section: A C V B V Boas E Colsunclassified